Preaching : communicating faith in an age of skepticism / ( Kept in the Circulation counter ) - Keller, Timothy, 1950-2023 (London, Hodder & Stoughton., 2015)
Presents a guide to preaching for pastors as well as laypeople, intended to help readers communicate the Christian message of grace in a meaningful, engaging, and compassionate way
Includes bibliographical references (pages 241-309)
Keywords: Preaching; Word of God (Christian theology); Communication -- Religious aspects -- Christianity